Pengembangan Website Coffe Shop – Kopi Om untuk media Promosi - Bramasto Wiryawan; Prihanto (Redtech Putra Benua, 2025)
Kopi Om, a coffee shop located in Surakarta, is a culinary business with significant market potential. Kopi Om has utilized social media for promotion and customer communication. However, its use of social media alone is considered suboptimal due to limitations in presenting comprehensive and structured information, such as a business profile, menu list, and integrated ordering access. Furthermore, the lack of an official website has resulted in the business's image being less than optimal as a professional brand in the digital age. To address these issues, an official website is needed to serve as a digital information and promotional tool for Kopi Om. This website is expected to display the coffee shop's profile, menu, and provide a direct ordering link to the online ordering service. With a website, customers can obtain information more clearly and quickly, and be directed directly to the ordering service without having to search for information through various separate platforms.